The changing character of the European banking market - Manfred Borchert (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2003)
At present West European banks are increasingly branching out into asset management as well as the consulting business, which cannot be directly influenced by monetary controls. We have therefore carried out a regression analysis and a factor analysis of banks' balance-sheet items, and we have also plotted figures from banks' income statements. Our analyses fulfil a triple purpose. First, they shed much light on the positioning strategies deployed by European banks. Second, they reveal different tendencies in respect of the refinancing strategies that are adopted when credits are granted to non-banks. Third, they make it possible to assess the effectiveness of monetary policy. There is clear evidence that the European Central Bank's money supply policy will prove less and less efficient as banks increasingly resort to refinancing by assets and continue to expand their banking services by building up their consulting businesses.
Keywords: E51; E58; G21; 330; Banking structure; Banking market; Banks' business strategies